2016
DOI: 10.1039/c5cy01479d
|View full text |Cite
|
Sign up to set email alerts
|

Perovskites and metal nitrides as catalysts in the base-catalysed aldol addition of isobutyraldehyde to formaldehyde

Abstract: Hydroxypivaldehyde represents an important intermediate in the production of neopentyl glycol, which in turn is widely applied in the production of e.g. polyesters, plasticizers, synthetic resin paints and lubricants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Using the temperature programmed desorption of carbon dioxide (CO 2 ‐TPD), we have investigated the basicity of the prepared mesoporous solid catalysts and are represented in Figure . The quantity of desorbed CO 2 and the temperature of maximum desorption are the criteria for the total basic sites and basic strength respectively . CO 2 ‐TPD of pure silica did show any CO 2 desorption peak in the studied temperature range, confirming that it has no basic sites .…”
Section: Resultsmentioning
confidence: 82%
“…Using the temperature programmed desorption of carbon dioxide (CO 2 ‐TPD), we have investigated the basicity of the prepared mesoporous solid catalysts and are represented in Figure . The quantity of desorbed CO 2 and the temperature of maximum desorption are the criteria for the total basic sites and basic strength respectively . CO 2 ‐TPD of pure silica did show any CO 2 desorption peak in the studied temperature range, confirming that it has no basic sites .…”
Section: Resultsmentioning
confidence: 82%
“…Catalytic transfer hydrogenation reaction (CTH) offers an efficient and safe route for hydrogenation of furfural to furfuryl alcohol (FOL), wherein organics (such as alcohols) rather than H 2 are served as hydrogen source in hydrogenation processes avoiding the risk in transportation and storage. A few researchers have reported that ABO 3 perovskite oxides shown catalytic activity in some liquid‐phase organic reactions, such as, acid/base‐catalyzed reactions, hydrogenation of aromatic nitro compounds and so on, which are attributed to their flexible crystal structure composition of metal ions at the A/B sites and surface chemical property [6, 34–36] . Importantly, our as‐prepared LaMnO 3 (LMO) with mesoporous nanocrystalline framework possesses rich oxygen vacancies and acid‐base sites with moderate strength on the basis of perovskite oxide structure.…”
Section: Introductionmentioning
confidence: 95%
“…[30][31][32][33] Catalytic transfer hydrogenation reaction (CTH) offers an efficient and safe route for hydrogenation of furfural to furfuryl alcohol (FOL), wherein organics (such as alcohols) rather than H 2 are served as hydrogen source in hydrogenation processes avoiding the risk in transportation and storage.Afew researchers have reported that ABO 3 perovskite oxides shown catalytic activity in some liquid-phase organic reactions,s uch as,a cid/base-catalyzed reactions, hydrogenation of aromatic nitro compounds and so on, which are attributed to their flexible crystal structure composition of metal ions at the A/B sites and surface chemical property. [6,[34][35][36] Importantly,o ur as-prepared LaMnO 3 (LMO) with mesoporous nanocrystalline framework possesses rich oxygen vacancies and acid-base sites with moderate strength on the basis of perovskite oxide structure.T hese are significant because the Lewis acid and base sites on catalyst are the key factors to catalyze the CTH reaction in the Meerwein-Ponndorf-Verley (MPV) mechanism, and oxygen vacancies can facilitate the interaction between carbonyl of substrate molecules and Mn sites in LMO catalyst. Fort hese unique nature of as-prepared LMO and combined with the results of previous researches,the CTH reaction is selected to probe the property of as-prepared mesoporous LMO catalyst and what contributes more to improved activity over catalyst will be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, catalyst shows high catalytic activity on continuous fixed reactor with high stability for 150 h (See Figure 28). [11a] …”
Section: Perovskites Mediated Organic Transformationsmentioning
confidence: 99%